From pandemic to pandemonium? Agrifood systems, coronavirus and Brazilian Public Health System - Carnut, Leonardo; Mendes, Áquilas; Guerra, Lúcia Dias da Silva (Argumentum, 2021)
This article aims to discuss the role of agrifood systems in shaping the coronavirus pandemic as an integral part of the totality of the capitalist crisis and its implication in the health area of Brazilian capitalism, in which the Bolsonaro government is witnessing the rise of ultraliberal and neo-fascist policies. Therefore, we opted for a historical-dialectical materialist analysis of the situation experienced between the world start of the pandemic until the month of May 2020 in Brazil. The article is structured in two parts: the first discusses the problem of agrifood systems in the context of capitalism in crisis and its effects on the spread of diseases such as the coronavirus, and the second discusses the neglect of the Bolsonaro government in facing the pandemic of the covid-19 and with the Brazilian universal health system.